PEMBELAJARAN DATA DAN STATISTIKA DASAR UNTUK ANAK SD - Nurhaswinda; Riska Putri Pilma; Rahmania Syahra Ramadhani; Nora Himayani; Nabila Arini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the learning of basic data and statistics in elementary school students and its importance in improving numeracy literacy and critical thinking skills. The method used is a literature study by analyzing various relevant scientific journals related to data presentation, measures of central tendency, and statistics learning in elementary schools. The results show that statistics learning plays an important role in helping students understand, process, and interpret data in a simple way. However, in its implementation, there are still several challenges, such as low conceptual understanding among students and the lack of varied teaching methods. Therefore, innovative, contextual, and interactive learning approaches are needed, such as the use of visual media and problem-based learning models. Thus, basic data and statistics learning is expected to enhance students' data literacy and critical thinking skills from an early age.